The Indo-Pacific axis peace and prosperity or conflict? - Chandra, S. (Satish); Ghoshal, Baladas 1943-; Society for Indian Ocean Studies; Taylor & Francis (Online service). (New Delhi Manohar, 2018)
Contributed articles presented at an international seminar organized by Society for Indian Ocean Studies.
Includes bibliographical references and index.
Keywords: Electronic books; Geopolitics -- Indo-Pacific Region -- Congresses; Indo-Pacific Region -- Strategic aspects -- Congresses; Indo-Pacific Region -- Foreign relations -- Congresses